"If It Lived Here, It Would Die." Children's Use of Materials as Semiotic Resources in Group Discussions About Evolution. Issue 3 (3rd July 2018) - Frejd, Johanna
ABSTRACT: With the aim of exploring how children discuss underlying reasons for evolution and how materials function in children's meaning making processes, this article provides insight into how evolution theory can be introduced in preschool and in the early years of primary school. Video data from eight group discussions ( N  = 27) were analyzed using a multimodal perspective. Despite not having had any formal instruction about evolution theory, the 6-year-old children in this study made use of their previous experiences and the materials to make meaning and argue for different reasons for animal diversity. The results show that the children's discussions concerned four conceptual themes: animals are different because of kinship and heredity, environmental effects, the need for adaptation, and the need for geographic separation. The children used the provided materials, comprising photographs, figurines, and a topographic world map, as resources for providing meaning, as argumentative tools, and as tools for communication. By making observations in a logical and scientific way, the children spontaneously discussed similarities and differences in traits, which implies that variation might be a fruitful way to introduce evolution theory to preschool children.